Response to Dr. Somovilla del Saz's letter to the editor regarding "Risk of all-cause and cardiac-related mortality after vaccination against COVID-19: A meta-analysis of self-controlled case series studies" - Greg J. Marchand; Ahmed Masoud (Taylor & Francis Group, 2023)
This is a response to Dr. Somovilla del Saz's letter to the editor regarding Marchand et al.'s article, "Risk of all-cause and cardiac-related mortality after vaccination against COVID-19: A meta-analysis of self-controlled case series studies." The response is on behalf of all authors clarifying misconceptions about the work.